ICTs in the acquisition of paremiological competence in Translation and Interpreting learners - Sevilla Munoz, Manuel; Huescar Villa, Myriam (Romanica Olomucensia, 2024)
The presence of phraseological units (PUs) in a text means a higher level of difficulty during the translation process. For this reason, it is desirable that learners of Translation and Interpreting acquire a certain phraseological and paremiological competence. The combined use of several ICTs could have a motivating effect on the teaching and learning process, enhance collaborative learning, and improve learning outcomes. On this point, a training action has been designed within the framework of the flipped classroom and collaborative learning so that Translation and Interpreting students can identify paremias, learn about their types, and characterise them. In this training activity, tutorial videos, Google Drive documents, and the Instagram social network, specifically the account of the Paremia journal, are used for didactic purposes. Once the educational action is over, students are given a questionnaire to assess the results of the final task, find out their opinion on how useful these ICTs are, and ascertain whether they favour collaborative learning and are motivated by it. The answers to the questionnaire are processed quantitatively. In general, the students obtained good results in the task and assessed the tutorial videos and the posts of the Instagram account positively as contents for self-learning prior to classroom practice. They perceived the Instagram account of the Paremia journal as a very motivating resource and the Google Drive documents as a tool that intensifies collaborative learning. It can be concluded that the combined use of the three ICTs implemented in this study (tutorial videos, Google Drive documents, and Paremia's Instagram account) boosts collaborative learning, improves student motivation, and facilitates the acquisition of paremiological competence.
Keywords: paremiology; ICT; flipped classroom; collaborative learning; translation